Peran Mediator Dalam Penyelesaian Sengketa Harta Warisan - Rani Ngadja; Barzah Latupono; La Ode Angga (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Settlement of disputes or conflicts that always occur in the community caused by inheritance, therefore gives rise to disputes and even causes conflicts between parties.Purposes of the Research: The purpose of this study was to determine the process of resolving inheritance disputes in the Religious Courts Class IA Ambon and how the role achieved by the mediator in the settlement of inheritance disputes in the Religious Courts Class IA Ambon. Methods of the Research: The research method used is Normative juridical research method with field research as primary data. The approach used is field research.Results of the Research: It can be concluded that the process of resolving Inheritance disputes at the Ambon Class IA Religious Courts is based on Law Number 7 of 1989 and the mediation guidelines of Government Regulation (PERMA) Number 1 of 2016. The mediator does not have the power to impose a settlement on the parties involved. dispute so that the role of the mediator is to negotiate until there is an agreement that binds the parties. The role of the Mediator in the mediation process is to mediate the parties, find common ground for the problems of the parties and oversee the course of mediation such as arranging negotiations, holding meetings, arranging discussions, mediating, formulating agreements between the parties so that mediation can be successful.